TANGGUNG JAWAB SOSIAL PERUSAHAAN (CORPORATE SOCIAL RESPONSIBILITY) DI BIDANG PERTAMBANGAN BAUKSIT PT. KERETA KENCANA BANGUN PERKASA TERHADAP LINGKUNGAN DAN MASYARAKAT KOTA TANJUNGPINANG - Derry Imanda Prima; Firdaus '; Dasrol ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Every company who standing and residing in Indonesia, specially company which active in mining was obliged to execute CSR pursuant to Pasal 74 ayat (1) Undang-Undang Nomor 40 Tahun 2007 Tentang Perseroan Terbatas explain that “Copartnership running it’s business activity in area and/or relate to natural resources was obliged to execute environmental and social responsibility”. Pursuant from the section, every company was obliged to budget and run CSR programs for society and environment.The CSR activity initially represent voluntary program and it was not obliged to be executed by company. This congeniality changes when government start to realize that CSR was very importance to be achieved, specially to company which active in mining. That’s happen because the mining companyis not care about society and environment in their operation area. The mining activity has destroyed the environmental and prosperity of society do not havea significant change which as commended by constitution.Theoritically, CSR begin from business ethics, where a company do not only having a legal and economic obligations to shareholders, but they also have obligation to other party (stakeholders). All of this rule is not get out of fact that the company cannot live, operated, and also obtain an advantage without stakeholders. CSR was showed the company’s caring for the importance of other party more than importance of the company itself. Company who consist to apply the CSR’s programs in their activity will obtain various advantage, one of them was the trust of stakeholders which representing a long term investment.Keywords: Corporate Social Responsibility, Environment, Society